Closed set speaker identification using fricative /s/ and /S/ in Kannada speaking individuals - Arjun MS; Hema N (Journal of All India Institute of Speech and Hearing, 1970)
The aim of the present study was to obtain the percentage of speaker veri cation using fricative sounds in Kannada speaking individuals. The participants chosen for the study were ten Kannada speaking neuro-typical adults, in the age range of 20-30 years, constituted as Group A and further sub grouped as Group B and Group C constituting ve malesand ve females respectively. The material used was eight commonly occurring, meaningful Kannada words containing the voiceless fricatives /s/ and /S/ in the word initial position. Spectrographic analysis using the PRAAT software was done and each token were measured for (1) the frication duration, (2) fricative amplitude ratio, (3) center frequencyof frication/turbulence. The results of the present study showed that fricative sound /s/ and /S/ was good for the condition - fricative duration with fricative amplitude (T2) which could be considered as an ecient parameter for speaker veri cation compared to other conditions.